2015
DOI: 10.21608/jappmu.2015.52963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flaxseed Oil on Digestibility, Blood Parameters, Immuno-Response and Productive Performance of Suckling Friesian Calves

Abstract: Aim of this study was to investigate the effect of flaxseed oil supplementation on the digestion, immunoglobulin concentration, some blood parameters, average daily gain, feed conversion and economic efficiency of suckling Friesian calves. A total of 28 newly born Friesian calves with weighing 31.42±1.9 kg were divided into two similar groups, 14 calves in each group. The first group (G1) was served as a control, while the second group (G2) was supplemented with 0.2 ml/kg LBW from flaxseed oil in suckling milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
6
5
0
Order By: Relevance
“…The long-term effects of mild deficiency are unclear, but it has been suggest that they include delayed wound healing, suboptimal immune functioning, increased plasma lipid peroxides and perhaps reduced taste and smell acuity seen in the elderly (Fortes et al 1997). The present values of serum total protein are within the normal range and in good agreement with those obtained by several investigators (Lee et al, 2008;Abu El-Hamd et al, 2015) on calves. Also, data revealed that concentration of TCH and LDL were significant declined with flaxseed oil ration compared with these of control ration.…”
Section: Biochemical Parameters In Bloodsupporting
confidence: 93%
See 4 more Smart Citations
“…The long-term effects of mild deficiency are unclear, but it has been suggest that they include delayed wound healing, suboptimal immune functioning, increased plasma lipid peroxides and perhaps reduced taste and smell acuity seen in the elderly (Fortes et al 1997). The present values of serum total protein are within the normal range and in good agreement with those obtained by several investigators (Lee et al, 2008;Abu El-Hamd et al, 2015) on calves. Also, data revealed that concentration of TCH and LDL were significant declined with flaxseed oil ration compared with these of control ration.…”
Section: Biochemical Parameters In Bloodsupporting
confidence: 93%
“…Flaxseed oil supplementation improved feed conversion ratio, which significantly (P<0.05) decreased the amounts of DM, TDN and DCP required for produce one kg 4% FCM in compared to control group. These results agreed with those obtained by Abu El-Hamd et al (2015) who found that feed conversion were significantly improved with flaxseed oil supplementation in Friesian calves as compared to the control group and Khattab et al (2011), who found that feed conversion values of buffalo calves were significantly better for groups supplemented by black seed oil than the other groups. Results of economic efficiency in Table (10) showed that average daily feed cost, price of 4% FCM yield, net revenue and net revenue improvement were significantly (P<0.05) higher for flaxseed oil supplemented group in than those of control group.…”
Section: Feed Conversion Ratio and Economic Efficiencysupporting
confidence: 91%
See 3 more Smart Citations